Review of control strategies for wave energy conversion systems and their validation: the wave-to-wire approach. (January 2018) - Wang, Liguo; Isberg, Jan; Tedeschi, Elisabetta
Abstract: Ocean waves are a promising source of renewable energy. In this paper, we briefly introduce the characteristics of ocean wave energy and summarize the principles of harvesting ocean energy by wave energy converters. We also review the prototypes or commercial devices deployed in real sea between 2005 and July 2016. In addition, we present the concept of a wave-to-wire model as a framework to systematically review and compare control strategies for wave energy conversion systems, with a focus on the numerical and experimental validation.